Combined strategies in the treatment of melasma. Case report - Mendoza Suarez, Elsa Maria (2024)
Melasma is a condition of symmetrical facial hyperpigmentation caused by melanin production issues, presenting as brown patches that can appear grayish or bluish, also affecting areas like the neck and décolletage. This aesthetic concern negatively impacts the quality of life and self-esteem of those affected. Hydroquinone is the most commonly used treatment, though various topical options exist. This article aims to describe the clinical case of a patient with melasma localized on the central facial region treated with a combined therapy, emphasizing patient adherence and commitment to dermatological care. Research indicates that the combination of hydroquinone, dermabrasion, and alpha hydroxy acids reduces hyperpigmentation, improves skin texture, achieving a more uniform and rejuvenated tone. Hydroquinone inhibits melanin production by blocking tyrosinase in dark spots. Dermabrasion enhances topical treatment absorption, while mandelic acid, an alpha hydroxy acid, improves skin texture without irritation due to its exfoliating and antimicrobial properties. In conclusion, the combined treatment of hydroquinone, dermabrasion, and alpha hydroxy acids is effective in treating facial melasma, as evidenced by the outcomes observed. This approach not only enhances aesthetic uniformity and rejuvenation but also underscores the importance of treatment adherence to achieve optimal benefits and enhance quality of life in patients with this skin condition.